Sheet-shaped honeycomb silicon nitride ceramic unit body and method for manufacturing the same

CN122520478BActive Publication Date: 2026-10-09安徽奥福精细陶瓷有限公司 +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610993006.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09
Estimated Expiration
2046-07-06

AI Technical Summary

Technical Problem

[0006]然而,目前的碳化硅蜂窝陶瓷普遍存在密度低、导热率低的问题,难以满足实际需求

Benefits of technology

[0019](1)本发明的片状蜂窝氮化硅陶瓷单元体,采用三级粒度配比的复合粉体体系,以粗颗粒的第一氮化硅粉作为骨架,中等粒度的第二氮化硅粉填充于第一氮化硅粉颗粒间的较大空隙中提高堆积密度,细颗粒的金属硅粉进一步渗入剩余微孔,熔融并实现致密化填充,将氮化硅颗粒粘连成三维网络结构最终反应形成硅结合相;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122520478B_ABST
    Figure CN122520478B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of honeycomb ceramics, in particular to a sheet-shaped honeycomb silicon nitride ceramic unit body and a preparation method thereof. The inorganic solid component in the raw material comprises first silicon nitride powder, second silicon nitride powder and metal silicon powder; the particle size of the first silicon nitride powder is larger than that of the second silicon nitride powder, the particle size of the second silicon nitride powder is larger than that of the metal silicon powder, and the mass percentage of the first silicon nitride powder in the inorganic solid component is greater than or equal to 60%. The raw material of the sheet-shaped honeycomb silicon nitride ceramic unit body is subjected to three-stage particle size grading, so that the honeycomb ceramic has high density and high thermal conductivity; meanwhile, the preparation process is simple, the yield is high; and the combined core component can effectively increase the energy exchange area between fluids and further improve the heat exchange rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of honeycomb ceramic technology, and more specifically, to sheet-like honeycomb silicon nitride ceramic units and their preparation methods. Background Technology

[0002] A heat exchanger is an energy-saving device that enables the transfer of heat between two or more fluids at different temperatures. It is essential for ensuring that the fluid temperature reaches the specified parameters of the process and is also one of the main devices for improving energy efficiency. The core component of a heat exchanger is the internal device that allows for heat exchange. The thermal conductivity of the heat exchanger determines its heat exchange efficiency, its high-temperature resistance affects its high-temperature resistance, and its thermal shock resistance directly affects its service life.

[0003] Traditional heat exchangers use stainless steel and other metals as their core components, which are far less heat-resistant than ceramic materials. Ceramic heat exchangers have the advantages of high temperature resistance, good thermal shock resistance, and long service life, and are therefore widely used in industries such as metallurgy, petrochemicals, food, pharmaceuticals, and environmental protection.

[0004] Currently, the main ceramic materials used in heat exchangers include mullite, alumina, cordierite, silicon carbide, and silicon nitride. Among them, silicon nitride has become the preferred material for ceramic heat exchangers due to its high temperature resistance, high thermal conductivity, good thermal shock resistance, and corrosion resistance.

[0005] Honeycomb structures are the preferred choice for fluid energy exchange. Extrusion molding is a simple and low-cost process for preparing honeycomb ceramics, making it easier to industrialize.

[0006] However, current silicon carbide honeycomb ceramics generally suffer from low density and low thermal conductivity, making it difficult to meet practical needs. Therefore, developing a low-cost, easily industrialized extruded silicon nitride honeycomb ceramic heat exchanger is a key technical challenge that needs to be addressed in ceramic heat exchanger development. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a sheet-like honeycomb silicon nitride ceramic unit and a method for preparing the same.

[0008] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: The present invention provides a sheet-like honeycomb silicon nitride ceramic unit, the raw material of which includes an inorganic solid component, wherein the inorganic solid component includes a first silicon nitride powder, a second silicon nitride powder and metallic silicon powder; Wherein, the particle size of the first silicon nitride powder is larger than that of the second silicon nitride powder, the particle size of the second silicon nitride powder is larger than that of metallic silicon powder, and the mass percentage of the first silicon nitride powder in the inorganic solid component is greater than or equal to 60%.

[0009] Based on the above technical solution, the present invention can be further improved as follows.

[0010] Furthermore, the particle size D of the first silicon nitride powder 50 The particle size is 30-40 μm, D 100 The particle size D of the second silicon nitride powder is less than or equal to 90 μm. 50 The particle size is 2-5 μm, D 100 The particle size D of the silicon metal powder is less than or equal to 20 μm. 50 The particle size is 1-3 μm, and the particle size D is... 100 Less than or equal to 15μm.

[0011] Furthermore, in the inorganic solid component, the mass percentage of the first silicon nitride powder is 60%-65%.

[0012] Furthermore, in the inorganic solid component, the mass percentage of the second silicon nitride powder is 15%-20%, and the mass percentage of the metallic silicon powder is 20%; and the sum of the mass percentages of the first silicon nitride powder, the second silicon nitride powder, and the metallic silicon powder is 100%.

[0013] Furthermore, the raw materials also include organic solid components and water, wherein the organic solid components include dispersants, binders, and lubricants; the binder is at least one of methylcellulose, hydroxypropyl methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, and polyvinyl alcohol; the dispersant is at least one of ammonium polyacrylate, ammonium polymethacrylate, ammonium citrate, and polyethylene glycol; and the lubricant is at least one of calcium stearate, white oil, base oil, glycerin, synthetic fatty acids, and water-soluble polyamide.

[0014] Furthermore, the mass of the binder is 9-12 wt% of the inorganic solid component, the mass of the dispersant is 0.5-2 wt% of the inorganic solid component, and the amount of lubricant added is 0.5-2.0 wt% of the total mass of the inorganic solid component, the binder, and the dispersant.

[0015] Furthermore, the sheet-like honeycomb silicon nitride ceramic unit has a single row or double row of holes, each hole penetrating the unit on the sheet-like plane, the axis of each hole being a straight line, and all holes arranged parallel to each other; the density of the sheet-like honeycomb silicon nitride ceramic unit is greater than 2.5 g / cm³. 3 The thermal conductivity is greater than 40 W / (m·K).

[0016] The present invention also provides a method for preparing a sheet-like honeycomb silicon nitride ceramic unit, wherein a clay segment is prepared using the raw materials described above, the clay segment is extruded into a honeycomb structure and microwave-dried and shaped to obtain a green body, and the green body is subjected to degreasing sintering and atmosphere sintering to obtain the sheet-like honeycomb silicon nitride ceramic unit.

[0017] Furthermore, the sintering process involves heating at a rate of less than 300°C / h within the range of room temperature to 800°C under the protection of inert and reducing gases, at a rate of less than 10°C / h within the range of 800°C to 1100°C, and at a rate of less than 5°C / h within the range of 1100°C to the holding temperature; the holding temperature is 1414°C to 1500°C, and the holding time is 4-6 hours.

[0018] The present invention also provides a core component of a silicon nitride honeycomb ceramic heat exchanger, comprising at least two layers of sheet-like silicon nitride ceramic units as described above, wherein the pore axes of adjacent layers of the sheet-like silicon nitride ceramic units are perpendicular to each other in the direction of the horizontal plane.

[0019] (1) The sheet-like honeycomb silicon nitride ceramic unit of the present invention adopts a composite powder system with a three-level particle size ratio. The coarse first silicon nitride powder is used as the skeleton, the medium-sized second silicon nitride powder is filled in the larger gaps between the first silicon nitride powder particles to increase the packing density, and the fine metal silicon powder further penetrates into the remaining micropores, melts and achieves densification and filling, and the silicon nitride particles are bonded into a three-dimensional network structure and finally react to form a silicon-bonded phase. (2) The sheet-like honeycomb silicon nitride ceramic unit of the present invention has a three-level particle size distribution, which makes the prepared honeycomb ceramic have high density and high thermal conductivity; (3) The sheet-like honeycomb silicon nitride ceramic unit body of the present invention, with a high proportion of first silicon nitride powder, not only ensures the high purity and high temperature resistance of silicon nitride ceramic, but also optimizes the uniformity and plasticity of the extrusion molding mud section through the synergistic effect of coarse and fine particles, avoiding the defects of the green body caused by fine powder agglomeration. (4) The sheet-like honeycomb silicon nitride ceramic unit of the present invention has the advantages of high density and high thermal conductivity, and the preparation process is simple and the yield is high; (5) The core component of the silicon nitride honeycomb ceramic heat exchanger of the present invention is obtained by combining sheet-like honeycomb silicon nitride ceramic units, which not only has high density and high thermal conductivity, but also its interlayer structure can effectively increase the area of ​​energy exchange between fluids, thereby further improving the heat exchange rate. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the double-row hole structure in the sheet-like honeycomb silicon nitride ceramic unit body of the present invention; Figure 2This is a schematic diagram of a single-row hole structure in the sheet-like honeycomb silicon nitride ceramic unit body of the present invention; Figure 3 This is a schematic diagram of the core component structure of the silicon nitride honeycomb ceramic heat exchanger of the present invention. Detailed Implementation

[0021] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0022] The sheet-like honeycomb silicon nitride ceramic unit of the present invention includes an inorganic solid component, which includes a first silicon nitride powder, a second silicon nitride powder, and metallic silicon powder; wherein the particle size of the first silicon nitride powder is larger than that of the second silicon nitride powder, the particle size of the second silicon nitride powder is larger than that of the metallic silicon powder, and the mass percentage of the first silicon nitride powder in the inorganic solid component is greater than or equal to 60%.

[0023] The sheet-like honeycomb silicon nitride ceramic unit of the present invention adopts a composite powder system with a three-level particle size distribution. The first silicon nitride powder with coarse particles serves as a skeleton to provide basic structural strength and occupies the main mass fraction to ensure high silicon nitride content, thereby ensuring the inherent high thermal conductivity of the material. The second silicon nitride powder with medium particle size fills the larger gaps between the first silicon nitride powder particles to increase the packing density. The fine silicon metal powder further penetrates into the remaining micropores and melts during the subsequent argon-protected sintering process, achieving densification and filling by means of capillary force, thus bonding the silicon nitride particles into a three-dimensional network structure and finally reacting to form a silicon-bonded phase.

[0024] This three-level gradient particle size design, based on the principle of closest packing, significantly reduces the porosity of the green body, resulting in high density and high thermal conductivity in the prepared honeycomb ceramics. At the same time, the high proportion of silicon nitride powder (not less than 60%) ensures the high purity and high temperature resistance of the silicon nitride ceramics, while the synergistic effect of coarse and fine particles optimizes the uniformity and plasticity of the extrusion molding mud segment, avoiding defects in the green body caused by fine powder agglomeration. Thus, a unity of high thermal conductivity, high density, and excellent molding processability is achieved.

[0025] Preferably, the particle size D of the first silicon nitride powder 50 The particle size is 30-40 μm, D 100 The particle size D of the second silicon nitride powder is less than or equal to 90 μm. 50 The particle size is 2-5 μm, D 100 Less than or equal to 20 μm; particle size D of metallic silicon powder 50 The particle size is 1-3 μm, and the particle size D is... 100The particle size distribution is less than or equal to 15 μm; the three-level gradient particle size design follows the principle of closest packing, and the particle size distribution ranges of each powder are clearly defined and non-overlapping, avoiding mutual interference and poor gradation between particles. It should be noted that the specific particle size values ​​mentioned above are based on the condition that the particle size of the first silicon nitride powder is larger than that of the second silicon nitride powder, and the particle size of the second silicon nitride powder is larger than that of the metallic silicon powder. Although the particle size D of the second silicon nitride powder... 50 Range and particle size D of metallic silicon powder 50 The ranges overlap, but when selecting specific values, the particle size D of the second silicon nitride powder should be ensured. 50 The particle size D is always greater than that of metallic silicon powder. 50 .

[0026] Preferably, the mass percentage of the first silicon nitride powder in the inorganic solid component is 60%-65%.

[0027] When the mass percentage of the first silicon nitride powder exceeds 65%, the filling space of the second silicon nitride powder and metallic silicon powder is insufficient. The gaps between particles cannot be fully filled by fine powder, resulting in a decrease in the degree of compaction. After sintering, the molten silicon cannot effectively penetrate and fill the pores, causing problems such as reduced green body density and low thermal conductivity. At the same time, too many coarse particles will reduce the plasticity of the clay, making extrusion molding difficult and causing crack defects due to insufficient green body strength. When the mass percentage of the first silicon nitride powder is less than 60%, the proportion of fine particles increases relatively. Although the packing density may increase in the short term, too much fine powder is prone to agglomeration, resulting in uneven clay segments, structural defects during extrusion molding, and increased specific surface area, leading to increased sintering shrinkage and difficulty in controlling dimensional accuracy. Therefore, the proportion range of 60%-65% is the key to achieving the best balance between high density, high thermal conductivity and excellent molding processability.

[0028] Preferably, in the inorganic solid component, the mass percentage of the second silicon nitride powder is 15%-20%, and the mass percentage of the metallic silicon powder is 20%.

[0029] When the mass percentage of the second silicon nitride powder is higher than 20%, the excessive amount of fine powder leads to agglomeration between particles, resulting in poor uniformity of the clay section, difficulty in extrusion molding, and the formation of many closed pores inside the green body. Although there is sufficient silicon melt after sintering, it cannot effectively penetrate into the micropore area blocked by fine powder, ultimately resulting in excessively low density and thermal conductivity, and severe deterioration of material properties. When the mass percentage of the second silicon nitride powder is lower than 15%, the particle size distribution is unbalanced, leading to a decrease in density after sintering. The density and thermal conductivity are also too low, and the plasticity of the clay is reduced, resulting in poor molding performance.

[0030] When the mass percentage of metallic silicon powder is higher than 20%, the excess silicon powder expands in volume during sintering, which not only makes it difficult to completely fill the pores but may also form local silicon-rich regions. The excessive proportion of silicon bonding phase leads to the dilution of the silicon nitride ceramic matrix, resulting in a decrease in the overall purity of the material. The inherent high thermal conductivity of silicon nitride is weakened, and both density and thermal conductivity are too low. Furthermore, the excess silicon may generate too many amorphous phases or abnormal grain growth after the reaction, affecting the thermal shock resistance. When the mass percentage of metallic silicon powder is lower than 20%, the total amount of silicon melt is insufficient to fully fill all the packing pores, and the compaction of the green body is incomplete. Although the density is high, the thermal conductivity is low.

[0031] Preferably, the raw materials also include organic solid components and water, wherein the organic solid components include dispersants, binders and lubricants; wherein the amount of water can be determined according to the actual situation.

[0032] The binder is at least one of methylcellulose, hydroxypropyl methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, and polyvinyl alcohol.

[0033] The binder is at least one of methyl cellulose (MC), hydroxypropyl methyl cellulose (HPMC), carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), and polyvinyl alcohol (PVA), and its addition amount is 9-12 wt% of the total mass of the inorganic solid components, preferably 10 wt%.

[0034] The dispersant is at least one of ammonium polyacrylate, ammonium polymethacrylate, ammonium citrate, and polyethylene glycol, and its addition amount is 0.5-2 wt% of the total mass of the inorganic solid components, preferably 1.5 wt%.

[0035] The lubricant is at least one of calcium stearate, white oil, base oil, glycerin, synthetic fatty acid, and water-soluble polyamide, and is added in an amount of 0.5-2.0 wt% of the total mass of mixture a, preferably 1.0%; mixture a is a mixture of inorganic solid components, binder, and dispersant.

[0036] The method for preparing sheet-like honeycomb silicon nitride ceramic unit of the present invention involves preparing clay segments from the raw materials described above, extruding the clay segments into a honeycomb structure and microwave drying and shaping to obtain a green body, and then subjecting the green body to degreasing sintering and atmosphere sintering to obtain sheet-like honeycomb silicon nitride ceramic unit.

[0037] In one embodiment of the present invention, the preparation method includes the following steps: S1. The first silicon nitride powder, the second silicon nitride powder, metallic silicon, binder and dispersant are mixed evenly by dry method to obtain mixture a.

[0038] S2. Add water and lubricant to the mixture a obtained in step S1 and knead it into mud blocks, then knead it into mud segments using a mud kneading machine.

[0039] S3. The mud segment obtained in step S2 is extruded into a honeycomb structure and microwave-dried and shaped.

[0040] Preferably, the microwave drying equipment has a working power of 40-60KW and a time of 20-30min.

[0041] S4. The green body from step S3 is degreased, sintered, and sintered in an atmosphere to obtain a sheet-like honeycomb silicon nitride ceramic unit.

[0042] Preferably, the degreasing sintering method is as follows: under an oxidizing atmosphere, the temperature is increased at a rate of less than 300℃ / h in the range of room temperature to 190℃, at a rate of less than 10℃ / h in the range of 190℃ to 260℃, and at a rate of less than 30℃ / h from 260℃ to the holding temperature, wherein the holding temperature is 400-550℃ and the holding time is 4-6h.

[0043] Preferably, the atmosphere sintering method is as follows: under the protection of inert gas and reducing gas, the temperature is increased at a rate of less than 300℃ / h in the range of room temperature to 800℃, at a rate of less than 10℃ / h in the range of 800℃ to 1100℃, and at a rate of less than 5℃ / h in the range of 1100℃ to the holding temperature; the holding temperature is 1414℃-1500℃, and the holding time is 4-6h.

[0044] The room temperature is 20-25℃.

[0045] The sheet-like honeycomb silicon nitride ceramic unit of the present invention is prepared by the method described above; as Figure 1 and 2 As shown, the sheet-like honeycomb silicon nitride ceramic unit has a single row or double row of holes, each hole penetrating the unit on the sheet-like plane, the axis of each hole is a straight line, and all holes are arranged parallel to each other.

[0046] Preferably, the density of the sheet-like honeycomb silicon nitride ceramic unit cell is greater than 2.5 g / cm³. 3 The thermal conductivity is greater than 40 W / (m·K).

[0047] The core component of the silicon nitride honeycomb ceramic heat exchanger of the present invention includes at least two layers of sheet-like honeycomb silicon nitride ceramic unit bodies as described above. Figure 3 As shown, the pore axes of two adjacent layers of sheet-like honeycomb silicon nitride ceramic units are perpendicular to each other in the horizontal direction.

[0048] Preferably, the core component of the silicon nitride honeycomb ceramic heat exchanger is obtained by splicing sheet-like honeycomb silicon nitride ceramic units together with a high thermal conductivity adhesive, followed by fine processing and skinning.

[0049] The effects of the present invention will be specifically illustrated below through specific embodiments and comparative examples.

[0050] The raw material composition ratios, densities, and thermal conductivity of each embodiment and comparative example are shown in Table 1. The dispersant and binder are calculated based on 100% of the total mass of the inorganic solid components, and the lubricant is calculated based on 100% of the total mass of mixture a.

[0051] In Examples 1-2 and Comparative Examples 1-4, the particle size D of the first silicon nitride 50 The particle size is 36 μm, and the particle size D is... 100 The particle size of the second silicon nitride is 86 μm; 50 The particle size is 4μm, and the particle size D is... 100 The particle size of metallic silicon is 15 μm; D 50 The particle size is 3μm, and the particle size D is... 100 It is 12μm.

[0052] In Comparative Example 5, the particle size D of the first silicon nitride 50 The particle size is 45 μm, and the particle size D is... 100 The particle size of the second silicon nitride is 101 μm; 50 The particle size is 6μm, and the particle size D is... 100 The particle size of metallic silicon is 25 μm; D 50 The particle size is 5μm, and the particle size D is... 100 It is 23μm.

[0053] Table 1. Raw material composition ratios and density and thermal conductivity of sheet-like honeycomb silicon nitride ceramic units in each embodiment and comparative example. The preparation processes for the above embodiments and comparative examples are as follows: S1. The first silicon nitride powder, the second silicon nitride powder, metallic silicon, binder and dispersant are mixed evenly by dry method to obtain mixture a.

[0054] S2. Add water and lubricant to the mixture a obtained in step S1 and knead it into mud blocks, then knead it into mud segments using a mud kneading machine.

[0055] S3. The mud segment obtained in step S2 is extruded into a honeycomb structure and microwave-dried and shaped.

[0056] The microwave drying frequency was 25 Hz, and the time was 28 minutes. S4. The green body from step S3 is degreased, sintered, and sintered in an atmosphere to obtain a sheet-like honeycomb silicon nitride ceramic unit.

[0057] The degreasing and sintering method is as follows: under oxidizing atmosphere conditions, the temperature is increased at a rate of 250℃ / h in the range of room temperature to 190℃, at a rate of 5℃ / h in the range of 190℃ to 260℃, and at a rate of 20℃ / h from 260℃ to the holding temperature, wherein the holding temperature is 500℃ and the holding time is 4h.

[0058] The atmosphere sintering method is as follows: under the protection of argon and reducing gas (H2 or CH4), the temperature is increased at a rate of 250℃ / h in the range of 25℃ to 800℃, at a rate of 8℃ / h in the range of 800℃ to 1100℃, and at a rate of 3℃ / h from 1100℃ to the holding temperature; the holding temperature is 1480℃ and the holding time is 4.5h.

[0059] The following conclusions can be drawn from the above test results: In Comparative Example 1, no dispersant was added. Although the ratio of 60% first silicon nitride powder, 20% second silicon nitride powder, and 20% metallic silicon powder was the same as in Example 1, the fine particles agglomerated due to a lack of effective dispersion, resulting in poor uniformity of the clay section. After extrusion molding, the interior of the green body contained many local defects caused by agglomerates. During sintering, the molten silicon could not penetrate and fill the cavity evenly, and the particles were not densely packed, resulting in a final density of only 2.21 g / cm³. 3 The thermal conductivity is 31 W / (m·k), which is significantly lower than that of Example 1, fully demonstrating the key role of the dispersant in the dispersion of fine particles and the final densification effect.

[0060] Comparative Example 2 increased the first silicon nitride powder to 70% and reduced the second silicon nitride powder to 10%. A large number of medium-sized voids between coarse particles were missing. The metallic silicon powder could not fill the voids at this scale due to its excessively fine particle size. The particle packing was severely unbalanced, the plasticity of the clay was reduced, and the density after sintering was significantly reduced. Compared with Example 1, the performance was significantly degraded, indicating that the gradation was severely deteriorated when the second silicon nitride powder content was below 15%.

[0061] Comparative Example 3 used excessive amounts of metallic silicon powder. After the metallic silicon powder melted, its volume expanded. Not only did it fail to further fill the pores, but it may also cause uneven sintering shrinkage due to local silicon enrichment. The excessive proportion of silicon-bonded phase diluted the silicon nitride matrix, resulting in a decrease in material purity. The content of high thermal conductivity silicon nitride phase was relatively reduced, and both density and thermal conductivity were low. This indicates that when the metallic silicon powder exceeds 20%, the densification mechanism changes from being dominated by filling to being dominated by reaction dilution.

[0062] In Comparative Example 4, the amount of second silicon nitride powder was increased to 25%, the amount of first silicon nitride powder was reduced to 55%, and the amount of metallic silicon powder was maintained at 20%. The excessive amount of fine powder led to severe agglomeration. The amount of dispersant was relatively insufficient, the uniformity of the mud segment was extremely poor, and extrusion molding was difficult. A large number of closed pores blocked by fine powder were formed inside the green body. The silicon melt could not penetrate into these areas. After sintering, the porosity increased, and the density and thermal conductivity were the lowest. This indicates that when the amount of second silicon nitride powder exceeds 20%, the agglomeration effect becomes the dominant factor restricting the performance.

[0063] The specific particle size of the inorganic solid component in Comparative Example 5 is not within the scope of the present invention. The particle size of the metallic silicon powder is similar to that of the second silicon nitride powder. It can be seen that the density and thermal conductivity of its silicon nitride honeycomb ceramic are both low.

[0064] In summary, the synergistic effect of the rational particle size distribution, the effective addition of dispersant, and the precise control of the content of each component determines the densification degree and thermal conductivity of silicon nitride honeycomb ceramics. The formulation scheme of Example 1 achieves the unity of the closest packing and the most complete densification.

[0065] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A sheet-like honeycomb silicon nitride ceramic unit, characterized in that, Its raw materials include inorganic solid components, which are composed of first silicon nitride powder, second silicon nitride powder and metallic silicon powder; Wherein, the particle size of the first silicon nitride powder is larger than that of the second silicon nitride powder, and the particle size of the second silicon nitride powder is larger than that of metallic silicon powder; the particle size D of the first silicon nitride powder... 50 The particle size is 30-40 μm, D. 100 The particle size D of the second silicon nitride powder is less than or equal to 90 μm. 50 The particle size is 2-5 μm, D 100 The particle size D of the silicon metal powder is less than or equal to 20 μm. 50 The particle size is 1-3 μm, and the particle size D is... 100 Less than or equal to 15 μm; In the inorganic solid component, the first silicon nitride powder has a mass percentage of 60%-65%, the second silicon nitride powder has a mass percentage of 15%-20%, and the metallic silicon powder has a mass percentage of 20%; and the sum of the mass percentages of the first silicon nitride powder, the second silicon nitride powder, and the metallic silicon powder is 100%. The raw materials also include organic solid components and water, wherein the organic solid components include dispersants, binders and lubricants; The sheet-like honeycomb silicon nitride ceramic unit has a single or double row of holes, each hole penetrating the unit on the sheet-like plane, with the axis of each hole being a straight line, and all holes arranged parallel to each other; the density of the sheet-like honeycomb silicon nitride ceramic unit is greater than 2.5 g / cm³. 3 The thermal conductivity is greater than 40 W / (m·K).

2. The sheet-like honeycomb silicon nitride ceramic unit body according to claim 1, characterized in that, The binder is at least one of methylcellulose, hydroxypropyl methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, and polyvinyl alcohol; the dispersant is at least one of ammonium polyacrylate, ammonium polymethacrylate, ammonium citrate, and polyethylene glycol; and the lubricant is at least one of calcium stearate, white oil, base oil, glycerin, synthetic fatty acid, and water-soluble polyamide.

3. The sheet-like honeycomb silicon nitride ceramic unit body according to claim 2, characterized in that, The mass of the binder is 9-12 wt% of the inorganic solid component, and the mass of the dispersant is 0.5-2 wt% of the inorganic solid component; the amount of lubricant added is 0.5-2.0 wt% of the total mass of the inorganic solid component, the binder, and the dispersant.

4. A method for preparing a sheet-like honeycomb silicon nitride ceramic unit cell as described in any one of claims 1-3, characterized in that, First, clay segments are prepared from raw materials. The clay segments are then extruded into a honeycomb structure and microwave-dried and shaped to obtain a green body. The green body is then degreased, sintered, and sintered in an atmosphere to obtain the sheet-like honeycomb silicon nitride ceramic unit.

5. The method for preparing a sheet-like honeycomb silicon nitride ceramic unit according to claim 4, characterized in that, The sintering process involves heating at a rate of less than 300°C / h within the range of room temperature to 800°C under the protection of inert and reducing gases, at a rate of less than 10°C / h within the range of 800°C to 1100°C, and at a rate of less than 5°C / h within the range of 1100°C to the holding temperature; the holding temperature is 1414°C to 1500°C, and the holding time is 4-6 hours.

6. A core component of a silicon nitride honeycomb ceramic heat exchanger, characterized in that, It includes at least two layers of sheet-like honeycomb silicon nitride ceramic unit cells as described in any one of claims 1-3, wherein the pore axes of two adjacent layers of the sheet-like honeycomb silicon nitride ceramic unit cells are perpendicular to each other in the direction of the horizontal plane.

Citation Information

Patent Citations

  • Honeycomb ceramic heat exchanger

    CN101493297A

  • Method for preparing silicon nitride particulate filter

    CN102172449A

  • Preparation method of silicon powder-doped silicon nitride ceramic substrate

    CN118754679A

  • Honeycomb ceramic support body for low-expansion high-temperature dust removal and preparation method of honeycomb ceramic support body

    CN121574007A